Characterization of a diamond-like carbon film produced from an electrosynthesized pre-ceramic polymer - Semra Ergen; Cemil Alkan; Orhan Uzun; Necati Başman (Journal of New Results in Science)
In this study, we aimed to prepare diamond-like carbon film from the electrosynthesized poly(hydridocarbyne) polymer and to investigate its surface, compositional and structural properties. The polymer was coated on Si substrate and then heated from room temperature to 1050 oC under argon atmosphere. More detailed characterizations than the previous studies revealed some new results. Surface morphology was examined by scanning electron microscopy. X-ray photoelectron spectroscopy analysis revealed that the film consisted of mainly carbon, with lesser percentages of oxygen, ferrum and silicium. From deconvolution of C 1s peak, sp3/sp2 ratio was found 0.55. Raman spectroscopy showed two broad bands at approximately 1347 cm-1 and 1597 cm-1, related to the D and G band of DLC, respectively. Furthermore, several peaks which were matched with the Fe3O4 and the Fe2SiO4 phase appeared in the Raman spectrum. Although these peaks were observed in the previous studies, they were not matched with any bound or structure. By means of analyses it was concluded that electrosynthesized polymer includes iron oxide due to the erosion of steel electrodes and this phase is also included in the DLC films produced from this polymer. Additionally, Fe2SiO4 is seen due to the reaction between iron oxide included in the polymer solution and Si substrate at the interface between the Si substrate and DLC film.